The Effect of Organizational Culture and Work Environment on Turnover Intention Through Organizational Commitment - Witasari, Rindi; Widhiandono, Hengky; Tubastuvi, Naelati; Rachmawati, Erny (International Journal of Business and Applied Economics, 2025)
This study aims to examine the effect of independent variables, namely organizational culture and work environment on the dependent variable, namely turnover intention and organizational commitment as a mediating variable. This study uses a quantitative research design. Questionnaires were distributed to employees of private hospitals in Purwokerto. The population in this study amounted to 327 employees. The sampling technique used in this study is the random sampling method in accordance with each member of the population has the same opportunity to be selected per field in the hospital. Calculated using the slovin formula resulted in 120 respondents. The method used to analyze data is to use smartpls 3.0. In this study all instruments were valid and reliable. The results showed that organizational culture has an insignificant negative effect on organizational commitment, but a significant positive effect on turnover intention. In contrast, the work environment has a significant positive effect on organizational commitment and a significant negative effect on turnover intention. Organizational commitment is not able to mediate the relationship between organizational culture and work environment on turnover intention.